A Particle-, Momentum-, and Energy-Conserving Fluid Transport Theory for the Tokamak Plasma Edge. (19th May 2019) - Stacey, Weston M.
Abstract: A particle-, momentum-, and energy-conserving, flux surface–averaged fluid theory for the radial particle and energy fluxes and the radial distributions of pressure, density, rotation velocities, and temperatures in the edge plasma that has been derived from fundamental fluid conservation (particle, momentum, energy) relations is summarized. Kinetic corrections arising from ion orbit loss are incorporated into the fluid equations, which are integrated to determine the dependence of the observed edge pedestal profile structure on fueling, heating, electromagnetic, and thermodynamic forces. Solution procedures for the fluid plasma and associated neutral transport equations are discussed.